2012
DOI: 10.1056/nejmoa1200111
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery versus Conventional Medical Therapy for Type 2 Diabetes

Abstract: In severely obese patients with type 2 diabetes, bariatric surgery resulted in better glucose control than did medical therapy. Preoperative BMI and weight loss did not predict the improvement in hyperglycemia after these procedures. (Funded by Catholic University of Rome; ClinicalTrials.gov number, NCT00888836.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
959
2
61

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,635 publications
(1,058 citation statements)
references
References 26 publications
(31 reference statements)
36
959
2
61
Order By: Relevance
“…Both surgical procedures resulted in greater improvement in other CVD risk factors, including triglycerides and HDL-C, compared with intensive medical therapy. Two other RCTs in patients with obesity and type 2 diabetes mellitus consisting of 60 102 and 120 103 patients demonstrated similar results. All 4 RCTs showed that surgery in the short term (1-2 years) was well tolerated, with few major complications, and resulted in both superior glycemic control and greater improvements in CVD risk factors compared with medical treatment alone in up to 24 months of follow-up.…”
Section: Effect Of Surgery On Glycemic Control Cvd Risk Factors Andsupporting
confidence: 54%
“…Both surgical procedures resulted in greater improvement in other CVD risk factors, including triglycerides and HDL-C, compared with intensive medical therapy. Two other RCTs in patients with obesity and type 2 diabetes mellitus consisting of 60 102 and 120 103 patients demonstrated similar results. All 4 RCTs showed that surgery in the short term (1-2 years) was well tolerated, with few major complications, and resulted in both superior glycemic control and greater improvements in CVD risk factors compared with medical treatment alone in up to 24 months of follow-up.…”
Section: Effect Of Surgery On Glycemic Control Cvd Risk Factors Andsupporting
confidence: 54%
“…A meta-analysis of observational studies of bariatric surgery involving 3188 patients with T2DM has reported that 78% had normalization of blood glucose in the absence of medications (14). However, available randomized trials are still very few and of limited size and duration (15,16). Furthermore, some recent observational studies have suggested caution about the benefits of bariatric surgery, showing no improvement in mortality when compared with standard care (17) and a high rate of long-term surgical complications especially for laparoscopic gastric banding procedures (18).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has a positive cost-benefit economic balance [6]. Moreover, a prospective study by Mingrone et al [7] has recently demonstrated that medical therapy, combined with bariatric surgery, controls glycaemic levels in more patients than medical therapy itself. In light of these findings, the Centres for Medicare and Medicaid Service (CMS), the American Diabetes Association (ADA), and IDF position statement [8] endorse bariatric surgery as the most effective treatment for obesity and several associated co-morbidities, such as type 2 diabetes mellitus [3].…”
Section: Introductionmentioning
confidence: 99%